Design, synthesis and characterisation of palladium-based bimetallic electrocatalysts for fuel cells and electrolyzers - Ipadeola, Adewale Kabir (My University, 2020)
This thesis describes the study of palladium (Pd)-based bimetallic electrocatalysts for alkaline direct ethanol fuel cell (ADEFC), fuel cell-based breath alcohol sensor (FCBrAS), alkaline water electrolyzer (AWE) and alkaline membrane fuel cell (AMFC). Metal-organic frameworks (MOFs) are synthesized and used as sacrificial templates for making novel MOF-derived carbons (MOFDCs) as supports for Pd-based electrocatalysts using microwave-assisted synthesis. The electrocatalysts are grouped into two: (i) Pd/SnO2-based nanostructured electrocatalysts (Pd/MOFDC and Pd/SnO2/MOFDC); and (ii) Pd/Ni-based nanostructured electrocatalysts comprising Pd on Ni-rich and Ni-starved MOFDC (i.e., Pd/Ni/MOFDC and Pd/AT-Ni/MOFDC, respectively). These Pd-based electrocatalysts are thoroughly examined using various state-of-the-art techniques including Raman, Brunauer-Emmett-Teller (BET) surface area analysis, powder x-ray diffraction (PXRD), x-ray photoelectron spectroscopy (XPS), and synchrotron analysis (XANES and EXAFS).For the electrochemical applications, various techniques were used, including cyclic voltammetry, (CV), chronoamperometry, linear sweep voltammetry (LSV), rotating (ring) disc electrode (RDE and RRDE) experiments and electrochemical impedance spectroscopy (EIS). The key reactions of interests for the two renewable energy fields (i.e., fuel cells and electrolyzers) include the ethanol oxidation reaction (EOR), hydrogen evolution (HER),oxygen evolution (OER), hydrogen oxidation (HOR) and oxygen reduction reactions (ORR). Amongst the electrocatalysts, the Pd/AT-Ni/MOFDC exhibits the best EOR activity and micro-ADEFC (peak power density = 24.49mW cm-2with68.0 % voltage retention after 24 h)and delivers good sensitivity and limit of detection for FCBrAS. In the AWE, the Pd/MOFDC exhibits better HER kinetics and energies than the Pd/SnO2/MOFDC while the Pd/SnO2/MOFDC displays high OER kinetics than the Pd/MOFDC. The addition of SnO2is detrimental for HER but beneficial for OER. The Pd/Ni/MOFDC has high HER and OER activities than the Pd/AT-Ni/MOFDC, due to the presence of Ni/Ni(OH)2interface advantageous for overall water electrolysis. However, Pd/MOFDC is the most active material for the HER amongst all the electrocatalysts investigated. In another scenario where HOR and ORR were investigated for the electrocatalysts, the Pd/SnO2/MOFDC shows extremely high HOR kinetics and stability with low energies than the Pd/MOFDC, but lower ORR kinetics. This result shows that the SnO2 addition suppresses the ORR activity. Interestingly, the Pd/AT-Ni/MOFDC displayed superior HOR and OER activities than the Pd/Ni/MOFDC. The Pd/AT-Ni/MOFDC shows best performance for HOR, while the Pd/MOFDC is best for ORR. The good performance of these novel Pd-based bimetallic nanostructured electrocatalysts bode well for their potential application in renewable energy conversion technologies, alkaline fuel cells and electrolyzers
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in the fulfilment for the degree of Doctor of Philosophy in Chemistry, 2020